Role of the immune modulator programmed cell death-1 during development and apoptosis of mouse retinal ganglion cells - Chen, Ling; Sham, Caroline W; Chan, Ann M; Francisco, Loise M; Wu, Yin; Mareninov, Sergey; Sharpe, Arlene H; Freeman, Gordon J; Yang, Xian-Jie; Braun, Jonathan; Gordon, Lynn K (Investigative ophthalmology & visual science, 2009)
Mammalian programmed cell death (PD)-1 is a membrane-associated receptor regulating the balance between T-cell activation, tolerance, and immunopathology; however, its role in neurons has not yet been defined. The hypothesis that PD-1 signaling actively promotes retinal ganglion cell (RGC) death within the developing mouse retina was investigated. Mature retinal cell types expressing PD-1 were identified by immunofluorescence staining of vertical retina sections; developmental expression was localized by immunostaining and quantified by Western blot analysis. PD-1 involvement in developmental RGC survival was assessed in vitro using retinal explants and in vivo using PD-1 knockout mice. PD-1 ligand gene expression was detected by RT-PCR. PD-1 is expressed in most adult RGCs and undergoes dynamic upregulation during the early postnatal window of retinal cell maturation and physiological programmed cell death (PCD). In vitro blockade of PD-1 signaling during this time selectively increases the survival of RGCs. Furthermore, PD-1-deficient mice show a selective increase in RGC number in the neonatal retina at the peak of developmental RGC death. Lastly, gene expression of the immune PD-1 ligand genes Pdcd1lg1 and Pdcd1lg2 was found throughout postnatal retina maturation. These findings collectively support a novel role for a PD-1-mediated signaling pathway in developmental PCD during postnatal RGC maturation.